The Role of Reading in the Development of Children's Psyche in Early Childhood - Ahunovna, Madgafurova Dilfuza (Research Parks Publishing LLC, 2022)
The article argues that the characteristics of the reading process serve as a basis for the further development of the child. Schooling enables children to develop their learning needs quickly and to acquire quality content, to develop an active interest in the world around them, and to acquire new knowledge and skills. It is based on scientific evidence that a child gradually begins to master his mental processes and learn to control his perception, attention and memory.